Extreme ST-segment elevations in seemingly no significant angiographic coronary artery abnormalities: a case report - Piels, M. (BMC Cardiovasc Disord, 2019)
BACKGROUND: Obstructive coronary artery disease is found in approximately 97% of patients presenting with ST-elevation myocardial infarction and 92% of patients with non ST-elevation myocardial infarction (Bainey KR, Welsh RC, Alemayehu W, Westerhout CM, Traboulsi D, Anderson T, et al. Int J Cardiol 264: 12–17, 2018). Recent studies showed that myocardial infarction without obstructive coronary atherosclerosis (MINOCA) is also associated with a long-term risk of adverse events (Bainey KR, Welsh RC, Alemayehu W, Westerhout CM, Traboulsi D, Anderson T, et al. Int J Cardiol 264: 12–17, 2018).. The following case illustrates that MINOCA may also be associated with short term adverse events (depending on the underlying mechanism). CASE PRESENTATION: A 49-year old Caucasian male with no significant medical history was referred to our cardiac emergency department with acute chest pain. The ambulance ECG showed extreme ST-segment elevation anterolateral (‘tombstone sign’), which had resolved completely at arrival in the hospital. Coronary angiography showed no obstructive coronary artery disease. Conservative (medical) therapy was started and patient was discharged. Two days later he presented with recurrent cardiac ischemia with ventricular fibrillation. Coronary angiography showed no changes compared with earlier presentation. During admission to the ICU his clinical condition gradually deteriorated, eventually leading to his death. Post-mortem studies showed no significant atherosclerotic lesions. Massive myocardial infarction was found, probably caused by temporary occlusion of the left main coronary artery. CONCLUSIONS: Several pathophysiological mechanisms are recognized in MINOCA, of which vasospasm is the most probable one in this case. MINOCA is associated with increased over-all mortality and risk of ventricular arrhythmias. Therefore, additional testing should be considered when there is no explanation for the mismatch between ST-elevations (STEMI) and (no significant) coronary abnormalities.